Sekolah Alam: Paradigma Baru Pendidikan Islam Humanis - Rohinah, Rohinah (FITK UIN Walisongo, 2014)
This paper describes a new paradigm of Islamic education in the perspective of humanism based on nature school model. This school model has three specific aspects, namely: natural as learning space, nature as media and teaching mate-rials, and natural as learning objects. It is a creativity in building a humanist paradigm of Islamic education. The education system emphasizes awareness to encourage the process of dialogue between teachers and students. Dialogical process can bring an attitude of humility and affection that is open to criticism from the learners. Learners are required critical and questioned again about the unknown by the teacher. This kind of learning led to a harmonious communica-tion between all parties. School of Natural allow the emergence of awareness. This school gives the freedom to create, explore and discover potential, and find the knowledge based on experiences from the world of reality.Â AbstrakMakalah ini menjelaskan paradigma baru pendidikan Islam dalam perspektif humanisme dengan bertolak pada model sekolah alam. Model sekolah ini memiliki tiga aspek khusus, yakni: alam sebagai ruang belajar, alam sebagai media dan bahan mengajar, serta alam sebagai objek pembelajaran. Pendidikan seperti ini merupakan sebuah kreativitas dalam membangun paradigma pendidikan Islam yang humanis. Sistem pendidikan ini menekankan penyadaran untuk mendorong adanya proses dialog antara guru dan anak didik. Proses dialogis dapat memunculkan sikap rendah hati dan kasih sayang sehingga terbuka terhadap kritik dari peserta didik. Peserta didik dituntut kritis dan mempertanyakan kembali tentang hal yang belum diketahui oleh sang guru. Pembelajaran semacam ini memunculkan kesadaran siswa dan komunikasi yang harmonis antara semua pihak. Sekolah ini memberikan kebebasan untuk berkreasi, menggali dan menemukan potensi, serta menemukan pengetahuan berbasis pada pengalaman-pengalaman dari dunia realitas.